Exploring the Role and Impact of Cultural Appropriation in the Fashion Industry - He, Yaqi (Transactions on Social Science, Education and Humanities Research, 2025)
Cultural appropriation is a general phenomenon in the fashion industry today, in which international brands appropriate cultural elements from marginalized groups without permission or compensation. This causes continuous public discussion and criticism of the fashion industry. This article uses typical examples such as Gucci's "blackface" sweater, Dior's "Sauvage" perfume advertisement, and Isabel Marant's use of Mexican Huipil embroidery as a starting point to analyze the phenomenon of cultural appropriation in brand fashion design. The article uses qualitative analysis and theoretical integration to examine the impact of cultural appropriation in the fashion industry on marginalized groups (ethnic minorities, indigenous communities, and religious groups). The results indicate that cultural appropriation often derives from unequal power structures between social groups and the lack of legal protection for traditional cultural expressions. This is leading to cultural devaluation, economic exploitation, and emotional harm toward marginalized groups. The article claims that brand companies should not use "borrowing inspiration" as an excuse for cultural appropriation. Instead, companies should shift toward collaborative and co-creation models with marginalized groups, and international organizations should enhance consumer awareness of cultural appropriation issues while addressing legal loopholes related to cultural copyright ownership, thereby protecting marginalized groups' cultural autonomy.